2019
DOI: 10.25115/psye.v11i1.2070
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del síndrome del burnout en piragüistas españoles de alto nivel: prevalencia en función de variables sociodemográficas y de la práctica deportiva

Abstract: Se analizó la prevalencia del síndrome de burnout en 77 piragüistas de alto nivel entre 17 y 24 años y la relación entre las puntuaciones de burnout y sus dimensiones y algunas variables sociodemográficas (sexo y edad) y de práctica deportiva (modalidad, categoría, años de práctica y volumen de entrenamiento). Para ello, los deportistas autocumplimentaron el Athlete Burnout Questionnaire. No se han encontrado casos de burnout, aunque alrededor del 10% de los piragüistas mostraron un riesgo moderado-alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Pedrosa and García-Cueto [ 54 ] reported a prevalence of around 3% in a sample of Spanish participants, values similar to those presented by Sanchez-Alcaraz Martínez and Gómez-Mármol [ 55 ] in a sample composed of Spanish and Spain-based tennis players with a prevalence of about 5%. Isorna Folgar et al [ 56 ] found no Spanish canoeists with BS but 10% of those studied showed a high risk of developing BS, while in Tutte and Reche [ 57 ] almost 5% of Spanish female hockey players presented BS and Olivares Tenza et al [ 58 ] found a 3% prevalence of BS in a Spanish athlete population. These significantly large differences in the reported prevalence of BS could be due to sport-specific reasons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pedrosa and García-Cueto [ 54 ] reported a prevalence of around 3% in a sample of Spanish participants, values similar to those presented by Sanchez-Alcaraz Martínez and Gómez-Mármol [ 55 ] in a sample composed of Spanish and Spain-based tennis players with a prevalence of about 5%. Isorna Folgar et al [ 56 ] found no Spanish canoeists with BS but 10% of those studied showed a high risk of developing BS, while in Tutte and Reche [ 57 ] almost 5% of Spanish female hockey players presented BS and Olivares Tenza et al [ 58 ] found a 3% prevalence of BS in a Spanish athlete population. These significantly large differences in the reported prevalence of BS could be due to sport-specific reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the inequality of disciplines, as well as the typology of efforts in competition, canoeing can be classified as an endurance sport, in which good aerobic capacity, aerobic efficiency at the anaerobic threshold, and lactic anaerobic capacity, especially lactate tolerance, are required to obtain a good performance (Fry and Morton, 1991;Faina et al, 1997). Therefore, canoeing is a sport where strength and endurance are developed together to optimize the athlete's performance (Bishop et al, 2002;Garcia-Pallares et al, 2009), factors that entail a greater training load, which can have an impact on the psychological aspect of athletes (Isorna Folgar et al, 2019).…”
Section: Effects Of Psychological Variables In Kayak Polomentioning
confidence: 99%